Helicobacter hepaticus Triggers Colitis in Specific-Pathogen-Free Interleukin-10 (IL-10)-Deficient Mice through an IL-12- and Gamma Interferon-Dependent Mechanism - Kullberg, Marika C. (American Society for Microbiology, 1998)
Mice rendered deficient in interleukin-10 (IL-10) by gene targeting (IL-10(−/−) mice) develop chronic enterocolitis resembling human inflammatory bowel disease (IBD) when maintained in conventional animal facilities. However, they display a minimal and delayed intestinal inflammatory response when reared under specific-pathogen-free (SPF) conditions, suggesting the involvement of a microbial component in pathogenesis. We show here that experimental infection with a single bacterial agent, Helicobacter hepaticus, induces chronic colitis in SPF-reared IL-10(−/−) mice and that the disease is accompanied by a type 1 cytokine response (gamma interferon [IFN-γ], tumor necrosis factor alpha, and nitric oxide) detected by restimulation of spleen and mesenteric lymph node cells with a soluble H. hepaticus antigen (Ag) preparation. In contrast, wild-type (WT) animals infected with the same bacteria did not develop disease and produced IL-10 as the dominant cytokine in response to Helicobacter Ag. Strong H. hepaticus-reactive antibody responses as measured by Ag-specific total immunoglobulin G (IgG), IgG1, IgG2a, IgG2b, IgG3, and IgA were observed in both WT and IL-10(−/−) mice. In vivo neutralization of IFN-γ or IL-12 resulted in a significant reduction of intestinal inflammation in H. hepaticus-infected IL-10(−/−) mice, suggesting an important role for these cytokines in the development of colitis in the model. Taken together, these microbial reconstitution experiments formally establish that a defined bacterial agent can serve as the immunological target in the development of large bowel inflammation in IL-10(−/−) mice and argue that in nonimmunocompromised hosts IL-10 stimulated in response to intestinal flora is important in preventing IBD.